Pembentukan Karakter Disiplin Peserta Didik pada Kegiatan Pramuka - Nadefa Ela Haqye; Sulastri (Indra institute Research & Publication, 2022)
Scout activities are one of the activities that can foster the disciplined character of students. However, there are still many students who do not understand character building, there are still many students who have not applied the character of discipline, there are still many scouting activities that have not been carried out in schools, and lack of education about the benefits of scouting. This study aims to determine the formation of the disciplined character of students through scouting activities in MTs. Serpong and the supporting and inhibiting factors for the formation of the disciplined character of students in scouting activities at MTs. Serpong. This research is a qualitative research, with the subject of this research includes the head of the madrasa, students, scout coaches and students. Data collection techniques using observation, interviews and documentation. The results showed that students who actively participated in scouting activities began to form disciplined characters such as increasing time discipline, being diligent, and obeying school rules. The supporting factors in scouting activities are with the support of school principals, experienced scout coaches and adequate facilities and infrastructure, besides that there are inhibiting factors in the formation of the disciplinary character of scouting activities, namely the lack of support from parents and the lack of understanding of the importance of scouting activities.